Demographic and functional potential of the Novosibirsk urban region in Russian Federation. A case study of transformations using the directional profile method - Tobiasz-Lis, Paulina; Wójcik, Marcin (Acta Universitatis Lodziensis. Folia Oeconomica, 2016)
The research presented in this article focuses on the urban region of Novosibirsk, which is one of the most industrialized part of Siberia and the Asian part of Russian Federation. To show relationships between the city as the core of the region and its peripheral area a case study analysing territorial units within the southern settlement belt along the Novosibirsk–Cherepanovo regional railway line over a distance of approx. 100 km. This belt was chosen because of the continuity of the settlement and due to the presence of different functional types of edge towns. The adopted system, from the core to the area of weakening direct links to Novosibirsk, helped to define the directional profile of the urban region as relating to the demographic and economic characteristics. The research was based on two methods of determining the functions of cities in the national settlement system: a research programme concerning the genesis of functional development and a research programme of specialised functions, the purpose of which is to determine the economic base (exogenous functions) of territorial units. The presented results have shown general tendencies in the transformations of the Novosibirsk urban region’s spatial structure, both in long-term perspective (the generic view of function development) and under contemporary circumstances related to the economic transformation of Russia.